Walking Humbly: Micah 6.8 Revisited - Dawes, S. (Scottish journal of theology, 1988)
The importance of this well-known verse has been frequently noted. It is cited as a high point in the literature of Israel, as a classic summary of the teaching of the eighth century prophets and as a statement of great lasting and theological value. In Jewish tradition it is used as one of the memorable summaries of the whole Law. It does contain, however, uncertainties of meaning and interpretation. In form it is a priestly or prophetic torah, giving an answer to the worshipper's question in vv. 6–7, What has a sinner to do to be restored to a right relationship with God, and then how is that relationship to be sustained? With a general statement like this questions of date and authorship are minor matters.